Transregional digital biglobalisation: methodology, theory, Eurasian practice - Gospodarik, Catherine G. (Journal of the Belarusian State University. Economics, 2024)
The article examines the main trends of the 21st century (biglobalisation, digitalisation and transregionalisation) and their impact on the EAEU and the Republic of Belarus. A detailed review of the literature is provided and problems for further scientiﬁc research are analysed. Factors contributing to biglobalisation are identiﬁed, diﬀerent stages of globalisation are distinguished based on export quotas, the impact of digitalisation on transregionalisation is analysed, and a mo del measuring the signiﬁcance of transregional associations is presented. Nine priorities for transregionalisation of the EAEU are proposed with a focus on new opportunities for the Republic of Belarus.